Palliative Care and Physician Assisted Death - Kőmüves, Sándor (ETHICS IN PROGRESS, 2022)
In the recent decade quite a few countries and regions legalised physician assisted death. While palliative care is already or becoming the standard end of life care in many countries, the increased availability of physician assisted death coupled with the secularisation of hospice in more settings require – where this has not happened yet – a clear response of palliative care specialists to patients’ requests for physician assisted death. The paper analyses the World Health Organisation’s current description of palliative care with a special focus on its prohibition of hastening death. Some palliative care professionals do not agree with the ban on hastening death, and these professionals’ non-conventional interpretation of palliative care actually seems to meet the wishes of some patients.